On the Generation and Regeneration of Retinal Ganglion Cells - Oliveira-Valença, Viviane M.; Bosco, Alejandra; Vetter, Monica L.; Silveira, Mariana S. (Frontiers in Cell and Developmental Biology, 2020)
Retinal development follows a conserved neurogenic program in vertebrates to orchestrate the generation of specific cell types from multipotent progenitors in sequential but overlapping waves. In this program, retinal ganglion cells (RGCs) are the first cell type generated. RGCs are the final output neurons of the retina and are essential for vision and circadian rhythm. Key molecular steps have been defined in multiple vertebrate species to regulate competence, specification, and terminal differentiation of this cell type. This involves neuronal-specific transcription factor networks, regulators of chromatin dynamics and miRNAs. In mammals, RGCs and their optic nerve axons undergo neurodegeneration and loss in glaucoma and other optic neuropathies, resulting in irreversible vision loss. The incapacity of RGCs and axons to regenerate reinforces the need for the design of efficient RGC replacement strategies. Here we describe the essential molecular pathways for the differentiation of RGCs in vertebrates, as well as experimental manipulations that extend the competence window for generation of this early cell type from late progenitors. We discuss recent advances in regeneration of retinal neurons in vivo in both mouse and zebrafish and discuss possible strategies and barriers to achieving RGC regeneration as a therapeutic approach for vision restoration in blinding diseases such as glaucoma.